Robust Consensus Controller Design for Nonlinear Relative Degree Two Multi-Agent Systems With Communication Constraints. - Münz, U; Papachristodoulou, A; Allgöwer, F (2011)
Robust static output-feedback controllers are designed that achieve consensus in networks of heterogeneous agents modeled as nonlinear systems of relative degree two. Both ideal communication networks and networks with communication constraints are considered, e.g., with limited communication range or heterogeneous communication delays. All design conditions that are presented are scalable to large and heterogeneous networks because the controller parameters depend only on the dynamics of the corresponding agent and its neighbors, but not on other agents in the network. © 2010 IEEE.